Ticks and tick-borne pathogens in South Bohemia (Czech Republic)--Spatial variability in Ixodes ricinus abundance, Borrelia burgdorferi and tick-borne encephalitis virus prevalence - Hönig, Václav; Svec, P; Halas, P; Vavruskova, Z; Tykalová, Hana; Kilian, P; Vetiskova, V; Dornakova, V; Sterbova, J; Simonova, Z; Erhart, J; Sterba, J; et al. (Ticks and tick-borne diseases, 2015)
Spatial distribution of Ixodes ricinus tick host-seeking activity, as well as prevalence of Borrelia burgdorferi sensu lato and tick-borne encephalitis virus (TBEV) were studied in the TBE endemic area of South Bohemia (Czech Republic). High variability in tick abundance detected in a network of 30 study sites was most closely associated with characteristics of vegetation cover. Of 11,182 tested tick samples, 12% carried DNA of spirochete from B. burgdorferi s.l. complex. B. afzelii and B. garinii prevailed among spirochete species. The presence of B. spielmanii in the region was confirmed. The median number of borrelial genome copies in positive samples reached 6.6 × 10(3) by real-time PCR. The total prevalence of TBEV in pooled samples reached 0.32% (20,057 samples tested), at least one TBEV positive tick was present in 21 out of 30 sampling sites.
Keywords: lymeská nemoc; Animals; Česká republika; Encephalitis Viruses, Tick-Borne; Ixodes; Female; Borrelia burgdorferi; zvířata; klíšťová encefalitida; mužské pohlaví; Male; klíště; Czech Republic; Lyme Disease; viry klíšťové encefalitidy; ženské pohlaví; Encephalitis, Tick-Borne